Modelo de Calidad de la Coordinación de Superación del Personal Académico de la Universidad de Guanajuato - Martínez, Patricia Catalina; Anguiano Maldonado, Cristina; Rico Venegas, Rosa María Rico Venegas (Acta Universitaria, 2005)
A Model of Quality: The Coordination of Continuous Academic Education (COSUPERA - Coordinación de Superación Académica). The University of Guanajuato through out time has undertaken different actions for orientation and reorientation of its work as well as establishing strategies that improve the development of the university functions and simplify the processes using methods that collaborate in the fulfillment of the institutional mission and the commitment of achieving academic excellence. This is realized through a number of departments and academic and administrative coordinations which aid the realization of this shared responsibility that we have been given. The Coordination of Continuous Academic Education (COSUPERA) is conscious of the above institutional commitment, which began in February 2001 to develop a strategic plan which contributes to achieving the quality of services of this coordination. From this began a series of activities such as: the elaboration of a diagnostic instrument used for the central program called “Strengths, Opportunities, Risks and Weaknesses” (FODA- Fuerzas, Oportunidades, Amenazas y Debilidades) where all of the workers participated in this coordination. Later a series of sessions were given to revise theoretical and methodological aspects of the quality programs emphasizing the systems of theory, processes, procedures, and user satisfaction, quality programs and statistics applied to the same processes. This was done so the group would understand that their participation in this program was fundamental to achieve the objectives.